The Role of Information and Informational and Communication Technologies in Modern Society. / El papel de la información y las tecnologías de la información y la comunicación en la sociedad moderna - Isachenko, Nadezhda N. (Utopía y Praxis Latinoamericana, 1970)
ABSTRACT The article presents the results of a study that determines the role of informational, communication and computer technologies in the development of modern society. The problems of the influence of informational, communication and computer technologies are considered in the framework of three theoretical and methodological approaches: technocratic, information and informational technology  recognizes as a means of optimizing production and increasing labor productivity; humanistic, information is considered as one of the resources that have a positive impact on the development of all spheres of life; techno-pessimistic, information, informational and computer technologies are consider as weapons directed against humanity.RESUMEN El artículo presenta los resultados de un estudio que determina el papel de las tecnologías de la información, la comunicación y las tegnologías de computador en el desarrollo de la sociedad moderna. Los problemas de la influencia de las tecnologías de la información, la comunicación y la computación se consideran en el marco de tres enfoques teóricos y metodológicos: la tecnología tecnocrática, la información y la tecnología de la información se reconoce como un medio para la capacidad de producción y el aumento de la pelea laboral; humanista, la información es considerada como uno de los recursos que tienen un impacto positivo en el desarrollo de todas las esferas de la vida; las tecnologías tecno-pesimistas, informáticas son consideradas como armas dirigidas contra la humanidad.